Socio-economic factors in relation to small ruminant farming' potential in Malaysia: ranchers' perspective - Yusoff, Melissa Alina; Man, Norsida; Mohd Nawi, Nolila (Zes Rokman Resources, 2016)
Small ruminant (goat and sheep) farming plays a significant role in economic development and improves the livelihood of ranchers. The contribution of the small ruminant industry to the agriculture productivity is becoming more substantial and significant. Hence, a study was conducted to observe the socio-economic characteristics of ranchers and production system of small ruminants. In addition, the relationship between socio-economic characteristics and the potential for small ruminant farming were determined. A total of six hundred (600) ranchers randomly selected from the eleven states of Malaysia to examine the socio-economic and farm profile of small ruminants. The survey was done by face to face interview through questionnaire. Simple percentages and frequency distribution tables were used to characterize and classify the data using the statistical package for social sciences (SPSS Version 21). The results showed that the highest number of respondents was involved between the ages of 40 to 50 years (23.5%), 92.8% were male and 7.2 % female. The married (86.7%) respondents and holding two family members were dominated in this industry. The majority of the ranchers were educated with less than five years of experience (36%), while a few (1.2 %) were illiterate in this farming. However, a significant (67.7%) of the respondents were keeping this industry as a part time job. Mostly land size of farms was less than 5 acres and dominated by owners’ farms (75.6%). Chi-square analysis showed positive significant relationship to variables with the number of animals and experiences except, age, gender, material status and part time job. Hence, small ruminant farming needs great intension by the government to develop appropriate polices for this industry. Moreover, government sector should encourage the participation of youth and women ranchers to participate and attract them by giving some subsidies like as poultry and oil palm industries.